2002
DOI: 10.1542/peds.110.5.855
|View full text |Cite
|
Sign up to set email alerts
|

Projected Cost-Effectiveness of Statewide Universal Newborn Hearing Screening

Abstract: The short-term cost-effectiveness of UNHS is comparable to the cost per case diagnosed of other newborn screening programs and could be improved by increasing the rate of follow-up to diagnostic evaluation after positive screening test results. If early identification results in improved language abilities, lower educational and vocational costs, and increased lifetime productivity, then UNHS has the potential for long-term cost savings compared with selective hearing screening and no screening. To understand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
133
0
10

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(150 citation statements)
references
References 44 publications
7
133
0
10
Order By: Relevance
“…9,10 Various studies have analyzed the cost of hearing screening in the neonatal period as well as the difference between the methods available. 11,12 The objective of the present study was to assess the The bivariate analysis revealed a statistically significant association between family history of congenital hearing loss and impaired AABR results, as well as for weight lower than 1,000 g, presence of genetic syndrome, asphyxia, presence of craniofacial malformation, occurrence of meningitis, use of ototoxic medication for more than five days and mechanical ventilation for more than five days (Table 1).…”
Section: Introductionmentioning
confidence: 96%
“…9,10 Various studies have analyzed the cost of hearing screening in the neonatal period as well as the difference between the methods available. 11,12 The objective of the present study was to assess the The bivariate analysis revealed a statistically significant association between family history of congenital hearing loss and impaired AABR results, as well as for weight lower than 1,000 g, presence of genetic syndrome, asphyxia, presence of craniofacial malformation, occurrence of meningitis, use of ototoxic medication for more than five days and mechanical ventilation for more than five days (Table 1).…”
Section: Introductionmentioning
confidence: 96%
“…Hearing loss can have devastating effects on children's lives 1 and incur large societal costs. 2 Therefore, despite methodologic flaws, 1 studies in the 1990s linking earlier diagnosis and management to better preschool language 3,4 drove large-scale implementation of new screening strategies (universal risk factor identification and universal newborn hearing screening [UNHS]) aiming to achieve much earlier detection and intervention than the existing opportunistic strategies, such as referral when a parent voiced concern about the child's hearing or language.…”
mentioning
confidence: 99%
“…8 Cost-effectiveness was supported by the only economic evaluation to consider long-term costs and outcomes of UNHS versus risk-factor screening but, in the absence of trials, this was based solely on projected improvements. 2 Two quasirandomized trials of UNHS have since been published. In the Wessex Study of 7-to 8-year-old English children offered UNHS in 1993-1996, neither expressive language nor speech clearly benefited; mean receptive language improved (effect size 0.56, 95% confidence interval [CI] 0.03-1.08) but remained nearly 2 SD below population norms.…”
mentioning
confidence: 99%
“…Pese al avance local, cada vez son más los estudios y evidencias de la esfera clínica, epidemioló-gica y económica que apuntan a la universalidad del programa, ya que se ha logrado identificar que los programas basados en la pesquisa dirigida en la población de mayor riesgo de hipoacusia dejan una gran proporción de casos sin diagnós-tico 4,11,[27][28][29][30][31] . Esta es una importante razón que justifica la implementación de programas de pesquisa que abarquen a la totalidad de los recién nacidos.…”
Section: Programas De Pesquisa En El Mundounclassified